DEMOCRATIC SHARIA: AN ISLAMIC LEGAL DISCOURSE IN AN ERA OF NATION-STATES - Ikhwan, Munirul (Universitas Islam Indonesia, 2018)
Modernization in the Muslim world has often been linked with the presence of European colonialism, which gained its strength from new forms of military and economic power. European colonial powers brought about an unprecedented disruption in the Muslim world, pushing it outside the hegemonic power. Muslim powers played insignificant or peripheral role in the world contestation of power; the “Islamic world” weakened and became “Islam in the world”. The modern West determined new concepts of humanity, history, society, and political legitimacy alien in the history of Islamic tradition. In this context, Muslims had to choose between two contrasting options, either to partake in the path of hegemonic modernity or to be isolated outside this dominant track.